Graded remapping of prefrontal representations preserves a cumulative record of distinct events within an environment - Yangzi Chen; Gaqi Tu; Lizhe Zhang; Kaori Takehara-Nishiuchi (iScience)
Summary: Motivationally significant events, such as rewards and threats, modify neural representations of the environment where they occur. The medial prefrontal cortex (mPFC) forms map-like representations anchored to these events. Using miniscope calcium imaging, we investigated how unexpected threats affected mPFC cell activity in mice, navigating a familiar path toward rewards. The introduction of threats increased the density of active cells near the threat location and triggered the emergence of a distinct population activity pattern that spanned the entire path. Notably, the difference between the new and original patterns was greater in the path segment leading to the new threats than in the segment leading to the existing rewards. This differentiation persisted during the subsequent learning of threat probabilities but ceased upon completion. Thus, event-induced remapping of mPFC population activity is scaled by the proximity to new events, enabling seamless integration of new events into the mental map of familiar environments.